Pendidikan Berbasis Life Skill di Pondok Pesantren - Rahim, Ainur (Al-Riwayah : Jurnal Kependidikan, 2016)
At least, there are three things that must be done by an educational institution to create quality education. The first is integrating a variety of subjects into an integrated learning activities and fun enjoy learning. The second is not only focusing on student intelligence, but also creating good character. The third is creating equality of teacher-student as subject of learners, including understanding students as a unique person with a different intelligence. The third element requires one important thing, namely, wise and insightful teachers with great academic ability and far-ranging experience. The application of life skills education in an educational institution will create students who have a good competitive output. With life skills education, they will be more productive and able to compete in the work world. Islamic boarding school takes the appropriate steps as it can prove that the Islamic boarding school is regarded as one of the competitive educational institutions. It is seen that the learning process is not only oriented to the intelligence of the students, but in the creation of noble character. In addition, most of Islamic teachers (ustadz) have been a degree scholar, even been doctor. This article elaborates the urgency of Islamic boarding school as a life skill education base.